Henrik Finály and Roman Dacia: The Contributions of a 19th Century Hungarian Po-Lymath to the Development of Roman Provincial Archaeology in Transylvania - Petruţ, Dávid (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
By any standards Henrik Finály was a true polymath, his overarching interests ranging from mathematics to classical studies, modern linguistics and literature, economics, medieval studies and archaeology. Although he was among the first Hungarian antiquarians to pursue systematic scholarly investigations of Roman Dacia, his contribution in this field has been unfairly downgraded in the intervening years, and his name almost erased from the research history of the province. The main goal of the paper is to provide a comprehensive insight into, and a critical overview of the early stages of Roman Dacia studies through the work of Henrik Finály in the social, political and cultural context of 19th century Transylvania.